SHAPING EXERCISES IN A PE CLASS STRUCTURE (An empirical research - Enver Međedović; Ahmet Međedović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Application of shaping exercises is related to good education of teachers that is especially related to form and function of entire organs, and also onto the use of energy and regular breathing. Through a co-author research, it has been observed important segments of presence of shaping exercises, the time of effective exercises observed through students' exercises of a younger school age, with an aim of determination of rational frequency in a preparation part of a class. By observing importance and a role of shaping exercises in PE classes from several aspects of values, in this work on a sample of 60 teachers of teaching education, a survey has been composed of 10 questions that are particularly related to opinions of teachers towards shaping exercises in the class structure. Through chosen methods of work (a descriptive and comparative method),that are in accordance with the very nature of this issue, the subject, the aim and tasks of the research, it has been established hypotheses.Received results have been processed and textually presented in tables and graph icons.